Peculiarities of pathogenesis of gastric cancer formed in the treatment of chronic non-atrophic gastritis by proton pump inhibitors - A. A. Avramenko; S. N. Smolyakov (Kazimierz Wielki University, 2018)
The data on the duration of use of proton pump inhibitors, the nature and duration of stress, and the timing of the first clinical and instrumentally confirmed manifestations of gastric cancer in 10 patients with chronic non-atrophic gastritis who were treated with proton pump inhibitors both in the form of monotherapy and the composition of standard regimens of H. pylori therapy. It was found that the duration of taking proton pump inhibitors ranged from 2 days to 2 months, and the duration of stress - from 2 years to 45 years. The first clinical manifestations occurred from the 1st to the 5th month after the end of the treatment, and the deterioration of the patients' condition proceeded quickly, "avalanche-like" within 7-10 days.